Endoscopic ultrasound-guided gastroenterostomy versus surgical gastrojejunostomy in treatment of malignant gastric outlet obstruction: Systematic review and meta-analysis - Bomman, Shivanand; Ghafoor, Adil; Sanders, David J.; Jayaraj, Mahendran; Chandra, Shruti; Krishnamoorthi, Rajesh (Endoscopy International Open, 2022)
Background and study aims Palliative treatment of malignant gastric outlet obstruction (GOO) has conventionally been with surgical gastrojejunostomy (SGJ). Advent of devices like lumen apposing metal stents has made endoscopic ultrasound-guided gastroenterostomy (EUS-GE) a potential alternative to SGJ for these patients. We performed a systematic review and meta-analysis of studies that compared outcomes of EUS-GE versus SGJ.Methods We performed a comprehensive systematic search of multiple electronic databases and conference proceedings through January 2021 and identified six studies that compared outcomes of EUS-GE versus SGJ in the management of malignant GOO. The rates of technical success, clinical success, and AEs were analyzed, and pooled odds ratios were calculated using random effects model.Results Six studies were included in our analysis with a total of 484 patients, of which 291 underwent EUS-GE and 193 underwent SGJ. The technical success rate of SGJ was superior to EUS-GE (OR = 0.195; 95 %CI:0.054–0.702; P = 0.012; I2 = 0). The clinical success of EUS-GE was statistically similar to SGJ (OR = 1.566; 95 %CI:0.585–4.197; P = 0.372; I2 = 46.68 %). EUS-GE had significantly fewer AEs compared to SGJ (OR = 0.295; 95 %CI:0.172–0.506; P < 0.005; I2 = 0). Among studies which reported reintervention rates, EUS-GE was statistically similar to SGJ (OR = 0.587; 95 %CI:0.174–1.979; P = 0.390, I2 = 54.91). Minimal to moderate heterogeneity was noted in the analyses.Conclusions EUS-GE has equivalent clinical success and reintervention rates, but significantly lower adverse events compared to SGJ. When feasible, EUS-GE appears to be an effective and safe alternative to SGJ for palliative management of malignant GOO.